Monitoring Suhu pada Infant Warmer Menggunakan INCU Analyzer Berbasis Arduino - Ningtias, Diah Rahayu; Wahyudi, Bayu; Harsoyo, Imam Tri (Universitas Semarang, 2021)
Temperature is the most important parameter in monitoring Infant Warmer medical equipment. In this study, temperature monitoring was carried out on the Lullaby GE Infant Warmer using INCU based on Arduino Uno. The temperature setting used was 34 ° C, 35 ° C, 36 ° C and 37 ° C with each setting repeated 3 times. The temperature sensor used in the INCU analyzer for T1 to T4 is DS18B20, while the T5 uses a DHT22 temperature sensor. At the Infant Warmer temperature, a low error value was obtained for all temperature settings, namely a temperature of 34 ° C with an error of 0.02, a temperature of 35 ° C with an error of 0.03, a temperature of 36 ° C with an error of 0.004 and a temperature of 37 ° C with an error of 0. The INCU analyzer output low temperature is at T5, with temperature settings of 34 ° C, 35 ° C, 35 ° C and 37 ° C respectively 0.009, 0.07, 0.11 and 0.28. While the error value on T1 to T4 ranges from 0.37, namely at T3 for a temperature setting of 35 ° C to 0.84, namely at T3 for a setting of 37 ° C. It can be concluded that the INCU analyzer that has a high degree of accuracy is the T5 using the DHT22 temperature sensor.